Efektivitas Gerakan Literasi Sekolah Sebagai Upaya Penanaman Karakter Berpikir Kritis Siswa SMP - Rindani, Aulia Nuri Najmi; Fauziah, Lafida Nisa; Rachman, Ichsan Fauzi (CV. ITTC INDONESIA, 2024)
Based on the report of the Ministry of Education, Culture, Research and Technology (Kemendikbud Ristek) in 2022 Indonesia has a literacy culture value of 57.4%. This figure shows that the literacy culture in Indonesia is still in the low category. This article was created to review and analyze the content of the articles that have been collected which aims to see the results of research on the effectiveness of the School Literacy Movement (GLS) as an effort to instill critical thinking characters in junior high school students. This article uses the literature study method. This technique combines theories and concepts into conceptual research methods. The analysis conducted in the literature study is content analysis. The literature study goes through various stages, such as forming opinions or arguments, providing criticism, determining the topic to be selected, conducting a literature survey, finding literature sources, then writing the results of the review. From each article that has been reviewed, it produces several things that become factors in the success of the School Literacy Movement (GLS) program in fostering critical thinking character in junior high school students.